2014
DOI: 10.4238/2014.october.31.24
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing identification of genes involved with Varroa destructor resistance in the eastern honeybee, Apis cerana

Abstract: ABSTRACT. Varroa destructor is the greatest threat to the honeybee Apis mellifera worldwide, while it rarely causes serious harm to its native host, the Eastern honeybee Apis cerana. The genetic mechanisms underlying the resistance of A. cerana to Varroa remain unclear. Thus, understanding the molecular mechanism of resistance to Varroa may provide useful insights for reducing this disease in other organisms. In this study, the transcriptomes of two A. cerana colonies were sequenced using the Illumina Solexa s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Indeed, transcripts of the calcium-transporting ATPase sarcoplasmic/endoplasmic reticulum (SERCA) and of the sarcalumenin were upregulated in CYp-infected insects. The former is a pump involved in translocation of cytosolic calcium into the sarcoplasmic reticulum to allow relaxation of muscle fibers (16); the latter is a calcium-binding protein involved in fine regulation of cellular calcium storage (52). Moreover, transcripts of the main proteins involved in contraction and cytoskeletal motion, namely, tropomyosin, troponin, myosin, actin, and dynein (16), were all upregulated upon CYp infection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, transcripts of the calcium-transporting ATPase sarcoplasmic/endoplasmic reticulum (SERCA) and of the sarcalumenin were upregulated in CYp-infected insects. The former is a pump involved in translocation of cytosolic calcium into the sarcoplasmic reticulum to allow relaxation of muscle fibers (16); the latter is a calcium-binding protein involved in fine regulation of cellular calcium storage (52). Moreover, transcripts of the main proteins involved in contraction and cytoskeletal motion, namely, tropomyosin, troponin, myosin, actin, and dynein (16), were all upregulated upon CYp infection.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, and in particular in China, beekeepers use the indigenous honey bee A. cerana in addition to non-native A. mellifera . The Asian honey bee has coevolved with Varroa mites ( Varroa jacobsoni and V. destructor ) and possesses behavioural 2730 and physiological resistance mechanisms against these mites 31 , which may protect them from the current global DWV epidemic 26 . At the same time, East Asia is the epicentre of disease emergence for bees: both the Varroa mite and the gut parasite Nosema ceranae have jumped from the Asian honey bee A. cerana to the European honey bee A. mellifera in East Asia in the last century and have spread globally.…”
Section: Introductionmentioning
confidence: 99%
“…The honey bee transcriptome in which we found the first Apis densovirus was erroneously classified as Apis mellifera carnica transcriptome (SRR922440, 52.177 con-tigs) and is still available under such name. It was produced from the whole heads of the workers by the researchers from the yangzhou University, Jiangsan Province, China (Ji et al, 2014). The analysis of the SRR922440 transcriptome showed that 86 % of contigs have strong signals to the Apis cerana and only 1.2 % to the Apis mellifera.…”
Section: Information About the Origin Of The Eastern Honey Bee Transcmentioning
confidence: 99%
“…This analysis demonstrated that the SRR922440 transcriptome originates from the Apis cerana, since numerous sequences show 99 % identity with the mitochondrial genome of A. cerana. The authors of this transcriptome (Ji et al, 2014) provided some information about the origin of the A. cerana colonies: M and C colonies were unrelated local strains in the same A. cerana population and were bred in the Guandong Entomological Institute, Guangzhou (also known in the West as the Canton), southern China. All Apis densovirus transcripts were obtained from the C colony that was Varroa resistant.…”
Section: Information About the Origin Of The Eastern Honey Bee Transcmentioning
confidence: 99%
See 1 more Smart Citation